SARS-CoV-2 infection as a potential risk factor for the development of cancer - Ogarek, Natalia; Oboza, Paulina; Olszanecka-Glinianowicz, Magdalena; Kocelak, Piotr (Frontiers in Molecular Biosciences, 2023)
The COVID-19 pandemic has a significant impact on public health and the estimated number of excess deaths may be more than three times higher than documented in official statistics. Numerous studies have shown an increased risk of severe COVID-19 and death in patients with cancer. In addition, the role of SARS-CoV-2 as a potential risk factor for the development of cancer has been considered. Therefore, in this review, we summarise the available data on the potential effects of SARS-CoV-2 infection on oncogenesis, including but not limited to effects on host signal transduction pathways, immune surveillance, chronic inflammation, oxidative stress, cell cycle dysregulation, potential viral genome integration, epigenetic alterations and genetic mutations, oncolytic effects and reactivation of dormant cancer cells. We also investigated the potential long-term effects and impact of the antiviral therapy used in COVID-19 on cancer development and its progression.